A novel systematic product ideation model using technology trends. Issue 3 (16th September 2020) - Tauqeer, Muhammad Ahmad; Bang, Knut Erik
Abstract : Purpose: This study aims to present a novel approach of using technology trends to trigger product ideas. It is primarily addressed to product ideation where limited applied approaches are available. Design/methodology/approach: The model is built by extending the theoretical framework of ideation study. It comprises morphological analysis with product breakdown as primary and technological trends as a secondary dimension to prompt product ideas from user's intuition. The approach is multidisciplinary using insights from the areas of cognition, management strategy and project management. The model is further tested in two different test configurations with university students ( n = 81). Findings: The results indicate that this systematic model can increase the quality and number of ideas generated by the students compared to generally practised approaches. It is shown that this approach increases the chances of triggering ideas. Research limitations/implications: The testing of the present model is comprehensive and in no means exhaustive. Practical implications: Because of the shrinking product life cycle, organisations have a need for systematic product ideation models that can assist in innovating their product ranges. It is important to study idea generation for products to not only assist product innovation but also comprehensively understand the process of creativity. The proposed model is primarily addressed to product innovation projects where limited practical tools are available for product ideation. The present model is easy to apply and has the tendency to generate novel product ideas that can lead to successful product innovations. Originality/value: Product innovation currently has limited systematic ideation tools where this study contributes.